Microplástico em ambientes recifais da costa do Ceará, Nordeste brasileiro - Barros, Yasmin Nascimento de (2024)
The presence of microplastics in the marine environment has been noted in scientificcirclessince the 1970s, and this is coupled with growing concern about howthese microparticlesinfluence the biotic and abiotic environment. In the marine environment, microplasticaccumulation points are considered sinks, such as ocean gyres and reef environments. Theaim of this work is to present the first record of microplastic found in the skeleton of aspeciesof reef-building coral in the South Atlantic and to test the hypothesis that proximitytoapolluted estuary and the population density of a region influence the presence of microplasticin the sediment of reef environments. The working area is the coast of the state of Ceará.Sediment was collected from five reef environments: Volta da Jurema (Fortaleza), FozrioCocó (Fortaleza), Pedra da Risca do Meio (Fortaleza), Canal do Uruau (Beberibe) andPedraRachada (Paracuru); and observed the influence of the mouth of the Maceió CreekonVoltada Jurema, the estuary of the Cocó River on Pedra da Risca do Meio and the reef at FozdoCocó, the estuary of the Ceará River on Pedra Rachada and the estuary of the JaguaribeRiveron Canal do Uruau. The corals were collected at Volta da Jurema (Fortaleza) andPedraRachada (Paracuru). For this, the methodology used is the extraction of microplastics, bydensity difference, present in the sediment, tissue and skeleton of the coral by a MicroplasticExtractor System (SEM); process followed by counting and photographic recordingbyastereoscopic microscope and chemical analysis by Raman spectroscopy. The results obtainedsupport the hypothesis that proximity to population centers and polluted estuaries influencethe amount of microplastics in the sediment and that there are microparticles in the skeletonofthe builder coral analyzed. This work contributes to the scientific community by providingaresearch base with data on microplastics in corals that has not yet been demonstratedonthecoast of Ceará, using a new methodology for extracting microplastics fromsedimentsandpresenting data that will help in the management of this ecosystem.